PENGOLAHAN LIMBAH UNTUK PERABOT INTERIOR RUMAH TINGGAL PONDOK PESANTREN AR ROUDHLOH NGRINGO PALUR KARANGANYAR - Sukirno Sukirno; Sunarmi Sunarmi (Abdi Seni, 2020)
This activity aims to give training and accompanying on interior ordering by using waste cardboard. The  activity  is  implemented  based  on  the  phenomena  in  the  pondok  (Muslim  boarding  school) showing that there is the same problem that is limitedness of room and furniture so that the bedroom is  not  conducive  for  studying.  The  activity  will  be  executed  in  Pondok  Pesantren  Ar  Roudhloh Ngringo Palur Karanganyar. The strategy used is the approach of demonstration and appreciation while the method used is speech, discussion, and direct practice. The application of the demonstration and appreciation method is hoped to be able to practice and give appreciation. Partner can directly practice in accordance to his capacity and also measure or give appreciation towards his own work as well as another work in his group maximally so that the services team can train and accompany them suitable to their needs in the field. The result covers: the activity has a positive impact, it can be seen from the rooms that change from the dirty rooms to the clean and tidy rooms even with the simple furniture. The main target of usage cardboard waste extends to the board of building waste which has been available in the Pondok. The success needs for about two months duration. At the beginning,  santri  (learners  at  Pondok)  is  not  interested  in  the  activity  but  finally  they  show  the positive reaction.Keywords: motivation, cardboard furniture, appreciation.